HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN IMUNISASI DASAR SESUAI JADWAL - Silvia Yasmin Lubis; Neila Hidayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
This study aims to see whether there is a relationship between the level of maternal knowledge and immunization according to the schedule. From 30 respondents, there were 3 people (10%) with low level of knowledge and 17 people (90%) with high level of knowledge. Then there are 12 people (40%) who are not compliant in carrying out immunizations and 18 people (60%) who are obedient in carrying out immunizations. While respondents with a high level of knowledge and obedience in carrying out immunizations were 17 people (30%) and respondents with a high level of knowledge but were not obedient in carrying out immunizations by 10 people (37%). Then respondents with a low level of knowledge and obedience in carrying out immunization were 1 person (33.3%), and respondents with a low level of knowledge but not compliant in carrying out immunizations were 2 people (66.7%). Then based on statistical analysis using the Chi Squre Test it can be concluded that, there is no relationship between the level of knowledge of mothers with basic immunizations according to the schedule at the banda aceh city health center.Keywords: Baby, Basic Immunization, Knowledge of Mother